Conformity of pre-gestational weight measurement and agreement of anthropometric data reported by pregnant women and those recorded in prenatal cards, City of Rio de Janeiro, 2007-2008 - Roberta Pereira Niquini; Sonia Azevedo Bittencourt; Maria do Carmo Leal (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
Objective: To assess the conformity of the weight measurement process in the pre-gestational care offered in the city of Rio de Janeiro by primary units and hospitals of the National Health System, as well as to verify the agreement between the anthropometric data reported by pregnant women and those recorded in prenatal cards. Method: A cross-sectional study was conducted in 2007 - 2008 with two cluster samples: one to obtain a sample of pregnant women to be interviewed and another one for the weight measurement procedures to be observed. The conformity of the weight measurement process was evaluated according to the Ministry of Health standards, and the agreement between the two sources of anthropometric data was evaluated using mean differences, Bland-Altman method, intraclass correlation coefficient (ICC) and weighted Kappa. Results: Out of the twelve criteria for weight measurement evaluation (n = 159 observations), three weren't in conformity (< 50% of conformity), two of them only need to be assessed when the scale is mechanical. For the interviewed pregnant women (n = 2,148), who had the two sources of anthropometric data, there was a tendency of self-reported height overestimation and pre-gestational and current weight and Body Mass Index underestimation. Accordance between the two sources of anthropometric information, according to ICC and weighted Kappa, were high (> 0.80). Conclusion: Studies may use weight and height information reported by pregnant women, in the absence of prenatal cards records, when it is an important economy to their execution, although the improvement of these two sources of information by means of better anthropometric process is necessary.